Paradigmatic relations of the Kazakh language: peculiarities of homonymous series. (Eurasian Journal of Philology Science and Education, 2015)
Homonyms have specific peculiarities in different languages. In the study of lexicology of modern Kazakh language homonyms do not create any difficulties for students. But if the educational manual given to students contains contradictory material on this subject, it will not lead to the qualitative acquisition of knowledge on homonyms. Therefore, when compiling the program on lexicology of modern Kazakh language it is necessary to systematize the study of homonyms and offer students a diverse theoretical and practical material. According to the general language process different meanings have various forms. However, the phenomenon of homonymy contradicts this concept. It is impossible to define homonyms separately. Homonymic features are seen only in the sentence and text materials. There are many examples in the Kazakh language that show polysemantic words are given as homonyms. One can notice the inner structure of homonyms in each homonymic series. Thus, we should pay attention to the semantic peculiarities of homonyms. We need to talk not only about the language nature of homonyms, but also in determining their national characteristics it is necessary to mention the homogeneous homonyms, which are a prime example of the semantics of words in the Kazakh language. The article also refers to the methods and techniques of studying homonyms in theacademic course.
Keywords: paradigmatic relations; lexicology; homonyms; innovation technology; homogeneous homonyms; polysemy; creative search